Prediction of Youth and Adult Recidivism Among Spanish Juveniles Involved in Serious Offenses - Cuervo, Keren (Criminal justice and behavior, 2020)
This study analyzes the predictive validity of the Youth Level of Service/Case Management Inventory (YLS/CMI) for youth and adult recidivism in a Spanish juvenile sample. Participants’ age ranged between 14 and 18.09 years old (N = 264) and 82% were boys and all had been sentenced to probation and custody centers. Data on juvenile and young adult recidivism were collected for the sample with mean follow-up periods of 13.74 and 20.19 months, respectively. The area under the curve, Kaplan-Meier and Cox regression survival analyses were each conducted to check for predictive validity. The findings demonstrated that the YLS/CMI is able to predict recidivism in both the juvenile period and the emerging adult period in a different cultural context. Prior Offenses and Education/Employment emerged as significant predictors for youth and young adult recidivism. The entire YLS/CMI is therefore an effective tool for risk classification in a different cultural sample.